Education and training for the oil and gas industry : the evolution of four energy nations : Mexico, Nigeria, Brazil, and Iraq /: the evolution of four energy nations : Mexico, Nigeria, Brazil, and Iraq. (2015) - (Owner, Getenergy Ltd.), Andrews, Phil; Playfoot, Jim; Augustus, Simon
No abstract available